Mengungkap Sejarah Manajemen Pendidikan Islam Pada Masa Khalifah Umar Bin Khattab - Suparman, Suparman (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
One of the four companions of the Prophet Muhammad SAW who was included in the khulafaurrasyidin was Umar bin Khattab. Umar bin Khattab was the second caliph after Abu Bakar Ash-Shiddiq. He was appointed by Muslims based on the recommendation of Abu Bakar Ash-Shiddiq when he felt that his age would not last long. The decision to appoint Umar bin Khattab is expected to be able to minimize the polemics that occur among Muslims. Because during the time of the caliph Abu Bakar Ash-Shiddiq there were many problems including: people did not pay zakat, apostates and false prophets emerged. During the reign of Umar bin Khattab, many areas were conquered in the Arabian Peninsula and outside the Arabian Peninsula. The conquest of Islam to various areas outside the Arabian Peninsula at that time gave rise to various changes that needed to be made in determining policies. This article describes in detail about Islamic civilization in the fields of religion, belief, politics, education, state administration and economics during the time of the caliph Umar bin Khattab. In this article, the use of library resources is prioritized, meaning that this article focuses on library research, because the analysis is directed at books and writings related to the discussion